2021
DOI: 10.1016/j.jhep.2021.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of COVID-19 vaccination in patients with non-alcoholic fatty liver disease (CHESS2101): A multicenter study

Abstract: Background & Aims The development of COVID-19 vaccines has progressed with encouraging safety and efficacy data. Concerns have been raised about SARS-CoV-2 vaccine responses in the large population of patients with non-alcoholic fatty liver disease (NAFLD). The study aimed to explore the safety and immunogenicity of COVID-19 vaccination in NAFLD. Methods This multicenter study included patients with NAFLD without a history of SARS-CoV-2 infection. All patients were vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 10 publications
12
99
1
5
Order By: Relevance
“…The previous history of SARS-CoV-2 infection was confirmed by reverse-transcription polymerase chain reaction, and antigen or antibody tests mainly using naso-oropharyngeal swabs. Cirrhosis was confirmed in all participants using clinical or biochemical evidence (splenomegaly, platelet count, ascites, hepatic encephalopathy, and/or variceal bleeding), FibroScan®, liver imaging, endoscopy or liver biopsy [ 8 , 11 14 ]. The splenomegaly was defined as the largest dimension of more than 11 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The previous history of SARS-CoV-2 infection was confirmed by reverse-transcription polymerase chain reaction, and antigen or antibody tests mainly using naso-oropharyngeal swabs. Cirrhosis was confirmed in all participants using clinical or biochemical evidence (splenomegaly, platelet count, ascites, hepatic encephalopathy, and/or variceal bleeding), FibroScan®, liver imaging, endoscopy or liver biopsy [ 8 , 11 14 ]. The splenomegaly was defined as the largest dimension of more than 11 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies analyzing immunogenicity in patients with impaired liver function showed similar results. In patients with non-alcoholic fatty liver disease (NAFLD), seropositivity rates of 95.5% were described [ 20 ]. In patients with liver cirrhosis, Thuluvath et al reported a seroconversion of 95.9% in a group of 79 patients with liver cirrhosis [ 21 ], and Calleri et al observed a seroconversion rate of 94.4% in 89 pre-transplant patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low immunogenicity of COVID-19 vaccine in liver transplantation were associated with factors of age, renal function and immunosuppressive medications ( Rabinowich et al, 2021 ). In contrast, a study demonstrated that NAFLD did not affect the efficacy of a COVID-19 vaccines ( Wang et al, 2021 , Wang et al, 2021 , Wang et al, 2021 ). It may be necessary to distinguish mild and severe liver diseases on vaccine efficacy ( Cornberg and Eberhardt, 2021 ).…”
Section: Intestinal Dysbiosis Linking Risk Factors To Inefficacy Of Covid-19 Vaccinesmentioning
confidence: 91%
“…1.351, P1 of B.1.1.28 and B.1.167 ( Jia and Gong, 2021 ). It has also been shown that antibodies isolated from natural infections and vaccinations are less effective against variants ( Chen et al, 2021 , Hoffmann et al, 2021 , Jia and Gong, 2021 , Khoury et al, 2021 , Röltgen et al, 2021 , Wang et al, 2021 , Wang et al, 2021 , Wang et al, 2021 ). A meta-analysis showed that neutralizing antibodies induced by natural infections or vaccinations had 1.5-fold reduction against B.1.1.7, 8.7-fold reduction against B1.351 and 5-fold reduction against P1 ( Chen et al, 2021 , Chen et al, 2021 ).…”
Section: Efficacy Of Covid-19 Vaccinesmentioning
confidence: 99%